From Eastern Bloc to European Union : comparative processes of transformation since 1990 - Heydemann, Günther 1950- HerausgeberIn; Vodička, Karel 1949-2021 HerausgeberIn (Studies in contemporary European history, 2017)
"More than 25 years after the fall of the Soviet Union, European integration remains a work in progress, especially in those Eastern European nations most dramatically reshaped by democratization and economic liberalization. This volume assembles detailed, empirically grounded studies of eleven states--Estonia, Latvia, Lithuania, Poland, the Czech Republic, Slovakia, Hungary, Romania, Bulgaria, Slovenia, and the former East Germany--that went on to join the European Union. Each chapter analyzes the political, economic, and social transformations that have taken place in these nations, using a comparative approach to identify structural similarities and assess outcomes relative to one another as well as the rest of the EU."--Provided by publisher